Religious thinking patterns and radicalism issues in students in Indonesian Public Universities - Surahman, Cucu; Mokh. Iman Firmansyah; Irfandi; Mohd Shafiee bin Hamzah (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
The issue of radicalism is often associated with religious understanding. The seeds of radicalism are also allegedly sown and growing among university students. This study aims to explore the religious thinking patterns of university students and the issue of radicalism in activists of the Islamic Student Activity Unit (Unit Kegiatan Mahasiswa, UKM) at Universitas Pendidikan Indonesia. This study uses a qualitative approach with a descriptive method. The primary data sources of this research are the results of observations, interviews, and documentation studies. The secondary data sources of this research are books, journal articles, mass media, and others related to the theme of this research. The data is processed through three stages: data reduction, data display, and conclusion drawn. This study shows that most activists of the Islamic Student Activity Unit (UKM Keislaman) at Universitas Pendidikan Indonesia have an inclusive and moderate mindset, and are not radical. However, there are also a small number of students who have an exclusive and radical style of religious thinking. Therefore, the guidance and control of the activities of UKM Keislaman, especially related to the issue of radicalism, as well as research on the development of religious patterns among students needs to be carried out simultaneously.